2017
DOI: 10.1080/14767058.2017.1340447
|View full text |Cite
|
Sign up to set email alerts
|

High- but not low-grade histologic chorioamnionitis is associated with spontaneous preterm birth in a Swedish cohort

Abstract: Despite a relatively low incidence of HCA in the preterm groups, HCA 2 seems to be associated with early preterm birth whereas HCA 1 seems to be part of the full-term delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Moreover, it has been found that high‐grade chorioamnionitis is over‐represented in stillborn term placentas and early preterm pregnancy compared to healthy controls , whereas low‐grade chorioamnionitis may be part of physiologic mechanism(s) in term pregnancy . In the present study, we find in the multivariate model an association between delivery at home and low‐grade chorioamnionitis.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, it has been found that high‐grade chorioamnionitis is over‐represented in stillborn term placentas and early preterm pregnancy compared to healthy controls , whereas low‐grade chorioamnionitis may be part of physiologic mechanism(s) in term pregnancy . In the present study, we find in the multivariate model an association between delivery at home and low‐grade chorioamnionitis.…”
Section: Discussionsupporting
confidence: 54%
“…Recent research has solidified our understanding of the significant contribution of the paternal parent to placental development in women and mice [8, 15-18, 58, 59]. Moreover, placental inflammation is an important determinant of the timing of parturition [38,60]; not surprisingly, premature placental inflammation has been associated with PTB [8,61,62]. Using a murine model, we previously found that premature placental inflammation and PTB frequently occur in association with a paternal history of developmental exposure to TCDD [8,9], a common environmental contaminant associated with combustion and known endocrine disruptor.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, increasing evidence indicated that there is a strong positive correlation between the infections in the genitourinary tract and the incidence of preterm birth, which consequentially lead to the preterm birth . Chorioamnionitis is one of the most common types of infections in the genitourinary tract during the period of pregnancy, and chorioamnionitis is also one of the leading causes of preterm birth . Results from previous studies indicated that if no proper medical interventions were made at the early stage of chorioamnionitis, premature delivery of the babies from mothers with chorioamnionitis can lead to short‐term and long‐term complications, that is, bronchopulmonary dysplasia (BPD), cerebral palsy (CP), and early‐onset sepsis (EOS) .…”
Section: Introductionmentioning
confidence: 99%